PENGEMBANGAN BUKU TENTANG PERADABAN ENERGI LISTRIK BERBASIS PJBL UNTUK MENUMBUHKAN KARAKTER SENANG BELAJAR - Sari, Cindy Gupita; Nugrahanta , Gregorius Ari (Jurnal Gentala Pendidikan Dasar, 2024)
A love of learning character is understood as a character that encourages an individual to experience positive feelings such as optimism, curiosity, persistence, consciousness, logic, competence, expertise, dedication, calmness, and confidence in acquiring new knowledge. Learning conditions that only prioritize academic knowledge over children's interests, talents, and potential are considered less effective learning, which can decrease the child’s authentic learning interest and even lead to a crisis. The aim of this research was to develop a book on electric energy civilization based on Project Based Learning to foster a love of learning character. The method used in this research was the ADDIE type of Research and Development (R&D). Ten certified teachers from different areas were involved in needs analysis, ten validators consisting of five experts and five teachers (practitioners) were involved for expert judgment, and eight children participated in limited product application testing. The results of the research showed that 1) books on electric energy civilization based on Project Based Learning to foster a love of learning character were developed using ADDIE measures; 2) the quality of the book fell within the “Very good” range (3.99 on a scale of 1-4) and did not require revision; 3) the application of the book had a significant influence on the love of learning character (p < 0.05) with a large effect size (r = 0.98), equivalent to 96%. The degree of efficiency of the application was high (N gain score = 94.264%).